Effect of concentration in two ion magnetized plasma sheath - Amgain, Suman; Neupane, Bijay Raj; Khadka, Narendra; Baniya, Smriti; Chalise, Roshan; Baniya, Hom Bahadur (SXC Journal, 2025)
The plasma sheath forms at the material wall surface in all practical plasma applications and plays a crucial role in the plasma-wall transition region. The influence of ion concentration in a magnetized plasma sheath containing two species of positive ions has been investigated using kinetic trajectory simulation. The study reveals that ion density, electron density, potential, and electric field decrease as they approach the wall, while the total charge density increases. An increase in ion concentration leads to a rise in ion density, electron density, total charge density, and potential, whereas the electric field decreases. Additionally, concentration variation in the plasma system affects the parametric values at the wall. Mathematically, ion density and total charge density exhibit exponential growth, while the electric field follows a parabolic function.